Registadores automáticos de baixo-custo para a monitorização de temperaturas do ar, da rocha e do solo - Viera, Gonçalo Teles; Mora, Carla; Ramos, Miguel (Finisterra, 2000)
LOW-COST DATA LOGGERS FOR AIR, SOIL AND ROCK TEMPERATURE MONITORING -Tiny Talk II data loggers were adapted in the laboratory of the Centro de Estudos Geográficos for air, soil and rock temperature monitoring. The loggers are single-channel 8 bit devices with a 2K EEPROM memory that allows the registration of 1,800 temperature records at user-defined intervals. Temperatures are measured by NTC100 thermistors separated by the authors from the data logger for more accurate measurements. Data is transfered from the loggers into a portable computer using a RS-232 cable. It is a low-cost system very appropriate for use in rough environmental conditions, particularly in mountain areas. It is successfully tested by the authors in the Antartic, Pyrenees, Sierra Nevada and Serra da Estrela.The detailed procedures for the construction of three measuring systems are described. The air temperature apparatus is constructed using PVC tubing and protecting cases and is designed for the measurement of air temperatures at 130cm above the ground. The soil temperature monitoring apparatus measures temperatures at 1, 5, 10 and 20cm depth and is based in 4 data loggers protected from moisture and dust in an IP68 case. The rock temperature measuring system is similar to the latter but the sensors are installed in the interior of the rock and isolated using silicon glue.